Population Pharmacokinetics of Lithium Carbonate in Young Male Healthy Chinese Volunteers - Yu, W.; Sun, X.; Li, Y.; Li, M.; Wang, K.; Li, H. (Pharmacopsychiatry, 2016)
Aim: To investigate the population pharmacokinetics (PK) model of lithium carbonate in young male healthy Chinese subjects.Methods: This study was conducted using a 2-period crossover design. 20 healthy male subjects received lithium carbonate tablets from 2 different Chinese pharmaceutical manufacturers. Plasma samples were obtained by blood sampling over 72 h in each period. Population PK analysis was performed using nonlinear mixed-effects model (NONMEM) software. The final models were validated using bootstrap and visual predictive check (VPC) approaches.Results: The final PK model was a two-compartment model. The population PK parameters, clearance (CL/F), apparent distribution volume of the central compartment (V2/F), inter-compartmental clearance (Q/F) and apparent distribution volume of the peripheral compartment (V3/F), were 9.39 L/h, 10.4 L, 22.1 L/h, and 216 L, respectively.Conclusion: Population PK models for lithium carbonate have been developed and considerable inter-subject variability was found in healthy young male Chinese subjects. It takes a long time to achieve the steady state in conventional therapy. This may provide guidelines for future use of lithium carbonate in China.
Keywords: lithium; healthy young male chinese subjects; population pharmacokinetics